Effects of the induced birefringence in photorefractive crystals on speckle optical vortices - Gómez, Jorge A. (2012)
In this work, we show that it is possible to change the properties of an optical vortex formed in a speckle pattern by the control of an external electric field applied to a sillenite-type photorefractive material in a non-holographic configuration. To show it, a scheme that allows the recovering of both, the polarization state and the phase distribution of an optical field was implemented. Changes in the polarization state of the light in the neighborhood of the vortex were observed with the application of an external electric field. Likewise, changes in the phase structure around the vortex and displacements of the vortices themselves were measured. These displacements have a fairly linear dependence on the applied field to the photorefractive crystal. Experimental results are qualitatively explained with the theoretical treatment of non-holographic recording in photorefractive crystals.